EFFECT OF GIVING PAPAIN ENZYMES ON COMMERCIAL FEED ON THE GROWTH AND SURVIVAL OF BAUNG FISH SEEDS (Hemibagrusnemurus) IN THE RECIRCULATION SYSTEM - Riska Rahmawati Harahap; Niken Ayu Pamukas; Rusliadi Rusliadi (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
ABSTRACT This research was conducted on February 20 - March 30, 2019 at the Laboratory of Aquaculture Technology, Faculty of Fisheries and Marine, University of Riau. This study aims to determine the best dosage of Papain enzymes mixed in commercial feed to see the growth and survival of baung fish. The research container used was a 60x40x40 cm3 aquarium with 15 aquariums with a stocking density of 15 fish / aquarium. This study used a Completely Randomized Design (CRD) with one factor of five levels of treatment and three replications. Each treatment was given the addition of papain enzymes as much as P1 (0 g / kg), P2 (0.25 g / kg), P3 (0.30 g / kg), P4 (0.35 g / kg), and P5 ( 0.40 g / kg) of feed. The results showed that the best treatment found in P4 (0.35 g / kg) of feed resulted in absolute weight growth of 5.84 g, growth of absolute length of 4.20 cm, specific growth rate of 4.56%, feed efficiency of 124.56% and livelihood 95.53%. Keywords: Papain Enzyme, Growth, Baung Fish (Hemibagrusnemurus)